Factors affecting the dynamics and heterogeneity of the EPR effect: pathophysiological and pathoanatomic features, drug formulations and physicochemical factors. (1st February 2022) - Islam, Rayhanul; Maeda, Hiroshi; Fang, Jun
ABSTRACT: Introduction: The enhanced permeability and retention (EPR) effect serves as the foundation of anticancer nanomedicine design. EPR effect-based drug delivery is an effective strategy for most solid tumors. However, the degree of efficacy depends on the pathophysiological conditions of tumors, drug formulations, and other factors. Areas covered: Vascular mediators including nitric oxide, bradykinin, and prostaglandins are vital for facilitating and maintaining EPR effect dynamics. Progression to large, advanced cancers may induce activated blood coagulation cascades, which lead to thrombus formation in tumor vasculature. Rapidly growing tumors cause obstructed or suppressed blood flow in tumor vasculature related to embolism or occluded blood vessels. The resulting limited tumor blood flow leads to less drug delivered to tumors, i.e. no or poor EPR effect. High stromal content also suppresses vascular permeability and drug diffusion. Restoring obstructed tumor blood flow and improving tumor vascular permeability via vascular mediators will improve drug delivery and the EPR effect. Physicochemical features of nanomedicines also influence therapeutic outcomes and are vital for the EPR effect. Expert opinion: The tumor microenvironment, especially tumor blood flow, is critical for a potent EPR effect. A rational strategy for circumventing EPR effect barriers must include restoring tumor blood flow.